2018
DOI: 10.1039/c8cp04272a
|View full text |Cite
|
Sign up to set email alerts
|

How does the electric current propagate through fully-hydrogenated borophene?

Abstract: We study the electronic transport properties of two-dimensional (2D) fully-hydrogenated borophene (namely, borophane), using density functional theory and non-equilibrium Green's function approaches. Borophane shows a perfect electrical transport anisotropy and is promising for applications. Along the peak- or equivalently the valley-parallel direction, 2D borophane exhibits a metallic characteristic and its current-voltage (I-V) curve shows a linear behavior, corresponding to the ON state in borophane-based n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…Most of the borophene sheets are metallic with remarkable anisotropy behaviors . They are proposed to be good electric conductors, even better than graphene according to theoretical calculations. Dirac cones are predicted to exist in β 12 , χ 3 and fully hydrogenated δ 6 borophene (borophane) sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the borophene sheets are metallic with remarkable anisotropy behaviors . They are proposed to be good electric conductors, even better than graphene according to theoretical calculations. Dirac cones are predicted to exist in β 12 , χ 3 and fully hydrogenated δ 6 borophene (borophane) sheets.…”
Section: Introductionmentioning
confidence: 99%
“…After the discovery of the well-known graphene, [1] a large number of two-dimensional (2D) monolayers (MLs) have been fabricated and studied, including silicene, [2,3] h-BN, [4] transition metal sulfides, [5][6][7][8][9][10] phosphorene, [11][12][13][14][15] MXene, [16,17] borophene, [18][19][20][21][22][23] stanene, [24] antimonene, [25] g-C3N4, [26,27] ferromagnets, [28,29] chromium trihalides CrX3, [30][31][32][33] and other graphene-like MLs. [34][35][36][37] Each type of these 2D materials possesses unique properties in mechanics, thermodynamics, optics, electrics, and magnetism.…”
Section: Introductionmentioning
confidence: 99%
“…The contour lines are drawn at 0.05 eV intervals in both electron (solid-navy) and hole-doped cases (dashedgreen).We demonstrate the band dispersion of borophane (Eq.2) in Fig. 2, where we have compared our used model Hamiltonian (Eq.1) with that calculations, based on the density functional theory and non-equilibrium Green's function approaches [35], the so-called NEGF-DFT method.…”
Section: Model Hamiltonian Of Borophenementioning
confidence: 92%
“…An et al using first-principles density functional theory plus the non-equilibrium Green's function approach, demonstrated that borophane displays a huge electrical and mechanical anisotropy. Along the valley-parallel direction (armchair), the 2D borophane exhibits a metallic treatment with a linear current-voltage curve, in contrast to the perpendicular buckled direction (zigzag), that shows off a semiconductor behavior [35].…”
Section: Introductionmentioning
confidence: 99%